1997
DOI: 10.1021/bi963030g
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 80 of Neurospora crassa, a Cytosolic Molecular Chaperone of the Eukaryotic Stress 90 Family, Interacts Directly with Heat Shock Protein 70

Abstract: The subunit structure of Hsp80, the most abundant heat-shock protein of Neurospora crassa, was examined by chemical cross-linking of the purified protein in vitro. Resolution of glutaraldehyde-treated Hsp80 by sodium dodecyl sulfate-polyacrylamide gel electrophoresis SDS-PAGE suggests that the native state of this protein is a tetramer; the relative proportion of cross-linked species, estimated by the fraction of protein recovered in each category, is consistent with a dimer-of-dimer structure. Upon interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…We have not observed any binding of hsp90 to hsp70 directly, in the absence of Hop. However, such an interaction has been suggested by chemical cross-linking studies (27) and has been observed directly with proteins from neurospora (64).…”
Section: Discussionmentioning
confidence: 99%
“…We have not observed any binding of hsp90 to hsp70 directly, in the absence of Hop. However, such an interaction has been suggested by chemical cross-linking studies (27) and has been observed directly with proteins from neurospora (64).…”
Section: Discussionmentioning
confidence: 99%
“…In Neurospora, however, cytosolic Hsp90 and Hsp70 have been shown to interact directly (Freitag et al, 1997). To test whether HSP90C and HSP70B may also interact directly, we mixed heterologously expressed HSP90C (0.012 mM) and HSP70B (0.015 mM) in the presence and absence of Mg-ATP in vitro.…”
Section: Hsp90c Interacts With the Chloroplast Chaperone Hsp70bmentioning
confidence: 99%
“…hsp90 is a functional homodimer with one homodimerization domain in the C terminus (17) and a second located within the N terminus (16). There are also a number of co-chaperone binding domains, including one for the acidic phosphoprotein p23, which binds to the amino-terminal and central region of hsp90 in an ATP-dependent manner (13, 18 -21) and one for other co-chaperones (15,(22)(23)(24)(25).The best characterized domain of hsp90 is the highly conserved, N-terminal, nucleotide-binding pocket (12,13,26), which also serves as the binding site for the hsp90 inhibitor geldanamycin (GA) (13,27). GA, a benzoquinone ansamycin antibiotic, exerts its inhibitory effect by blocking the ATP-dependent binding of p23 to hsp90 (12, 13).…”
mentioning
confidence: 99%
“…hsp90 is a functional homodimer with one homodimerization domain in the C terminus (17) and a second located within the N terminus (16). There are also a number of co-chaperone binding domains, including one for the acidic phosphoprotein p23, which binds to the amino-terminal and central region of hsp90 in an ATP-dependent manner (13, 18 -21) and one for other co-chaperones (15,(22)(23)(24)(25).…”
mentioning
confidence: 99%